2020
DOI: 10.1155/2020/8814545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sea-Level Change on Deep-Sea Sedimentary Records in the Northeastern South China Sea over the past 42 kyr

Abstract: We integrated multiple geochemical analysis of a 13.75 m-long core 973-4 recovered from the northeastern South China Sea (SCS) to detect the response of deep-sea sediment archives to sea-level change spanning the last 42 kyr. The age-depth model based on AMS 14C dating, together with the sediment grain size, shows an occurrence of turbidity current at around 14 kyr, which was associated with submarine landslides caused by gas hydrate dissociation. A dominantly terrigenous sediment input was supplied from south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(144 reference statements)
0
0
0
Order By: Relevance
“…Rapid sedimentation together with sea level variations, landslides, and turbidity currents inevitably induces the simultaneous reaction of GH. The GH formation in the upper and middle layers of the sedimentary layer and decomposition in the lower part occurred [57,59]. Huge thick unconsolidated sedimentary seabed breeds and traps large amounts of methane-rich overpressure pore fluids.…”
Section: Multiple Accumulation Assumptionmentioning
confidence: 99%
“…Rapid sedimentation together with sea level variations, landslides, and turbidity currents inevitably induces the simultaneous reaction of GH. The GH formation in the upper and middle layers of the sedimentary layer and decomposition in the lower part occurred [57,59]. Huge thick unconsolidated sedimentary seabed breeds and traps large amounts of methane-rich overpressure pore fluids.…”
Section: Multiple Accumulation Assumptionmentioning
confidence: 99%
“…In different regions, the sedimentary factors that control the TOC content may also vary greatly [5,40,41]. For example, some studies suggest that the higher the productivity level in marine sediments, the higher the TOC content [42], but some studies have found that the TOC content sometimes shows an opposite trend to marine productivity indicators [16,43]. The sedimentary condition is not unidirectional for regulating the TOC content.…”
Section: Introductionmentioning
confidence: 99%